Furfuryl palmitate emollient in pediatric atopic dermatitis: real-world case report - Katke, Vaishali; Girdhar, Mukesh; Banerjee, Ritwik (International Journal of Research in Medical Sciences, 2026)
Atopic dermatitis (AD) is a chronic inflammatory disease that can be characterized by impaired barrier dysfunction, immune dysregulation, and oxidative stress. While long-term corticosteroid therapy is effective for the treatment of AD, safety concerns often limit use and contribute to poor adherence, especially in children, thus compelling the need for safer, non-steroid options. Furfuryl palmitate, a strong antioxidant with skin barrier-protective properties, has been shown to reduce oxidative damage and inflammation in AD. This case report focuses on two children, aged 4 and 9 years, with moderate AD [eczema area and severity index (EASI) scores 18-19.5] treated with Relizema® cream, which contains furfuryl palmitate. They received it either as ongoing treatment after stopping corticosteroids or along with calcineurin inhibitors. Between 3 and 6 months of treatment, both children demonstrated significant clinical improvement, including improvement in erythema, pruritus, and lichenification, and there were no adverse effects or disease flares. Improvements were also noted in sleep quality, emotional well-being, and caregiver stress. The dual mechanism of hydration and modulation of oxidative stress with furfuryl palmitate is an effective strategy for long-term management of AD to maintain long-term remission, while increasing adherence. This case report supports furfuryl palmitate in the cream form as an effective, well-tolerated, non-steroid option for pediatric patients with AD, and furfuryl palmitate cream is another valuable resource for long-term proactive management of AD that aims to restore the barrier function of the skin and prevent relapses of AD.